Longitudinal evolution of physical activity during and after chemotherapy for breast cancer. Issue 1 (4th January 2021) - Girouard, Alice; Michel, Alexandra; Ouellet, Marie-Michèle; Guimond, Anne-Josée; Ruel, Sophie; Ivers, Hans; Savard, Josée
Abstract: Background: Previous research has found that, on average, breast cancer patients tend to become less active during chemotherapy and to increase slightly their physical activity (PA) level afterwards. However, patients may show distinct trajectories of PA during and after chemotherapy. Objectives were to: investigate the global evolution of PA before (T1), during (T2), and after chemotherapy (T3), as well as 3 (T4) and 6 (T5) months later; document the distinct trajectories of PA from T1-T5; and explore the moderating effect of the initial PA level on subsequent PA trajectories (T2-T5). Methods: Fifty breast cancer patients ( M age = 55.1, SD  = 10.4) wore an actigraph for 7 consecutive 24-hour periods to measure the time spent in moderate-to-vigorous PA and completed the Godin Leisure-Time Exercise questionnaire (GLTEQ) at 5 time points. Results: At baseline, participants showed an average of 8.8 minutes of objectively measured moderate-to-vigorous PA per week and a mean score of 20.4 (moderate PA) on the GLTEQ. A significant time effect (i.e., increase) was obtained on both measures when analyzing the total sample ( P  = .001; P  = .021, respectively). Latent class growth modeling revealed 2 distinct trajectories ("mild-to-moderate PA" and "strenuous PA") of PA for the subjective measure, and 4 trajectories ("very low and stable MVPA, " "very low and slightly increasing MVPA, " "very low and highly increasing MVPA, " and "low and slightly decreasing MVPA") for the objective one. With regards to the moderating role of baseline PA levels, no significant group X time interactions were found for the subjective and objective measures ( P  = .077 and.10, respectively). Conclusions: The evolution of PA during and after chemotherapy is variable across patients. However, it remains challenging for everyone to remain or be active during chemotherapy. More research is needed to design more effective PA intervention in this population.